2021
DOI: 10.3389/fmicb.2021.602135
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermentation With Aspergillus cristatus Enhances the Protopanaxadiol- and Protopanaxatriol-Associated Skin Anti-aging Activity of Panax notoginseng

Abstract: A metabolomics approach was used to profile metabolites of Panax notoginseng fermented with Aspergillus cristatus in two ways, liquid-state fermentation (LF-P) and solid-state fermentation (SSF-P) and examine metabolite markers representing antioxidant activity and skin anti-aging. Protopanaxadiol (PPD) and protopanaxatriol (PPT) contents were higher in SSF-P than in LF-P and showed a multiplicative increase over the fermentation period of four days. PPD and PPT levels also correlated with antioxidant and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Similarly, the solid-state fermented Panax notoginseng by Aspergillus cristatus reduced the contents of ginsenosides Rb1, Rb2, Rc and Rd. ( Lee et al, 2021 ). Our results showed that the fermentation of E. cristatum leaded to the degradation of saponins in WG, and the hypoglycemic effect can be improved by changing the saponin contents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the solid-state fermented Panax notoginseng by Aspergillus cristatus reduced the contents of ginsenosides Rb1, Rb2, Rc and Rd. ( Lee et al, 2021 ). Our results showed that the fermentation of E. cristatum leaded to the degradation of saponins in WG, and the hypoglycemic effect can be improved by changing the saponin contents.…”
Section: Discussionmentioning
confidence: 99%
“…A FRAP assay was performed according to Benzie and Lee with minor modifications ( Benzie and Strain, 1996 ; Lee et al, 2021 ). The reducing capacity of WG extracts was calculated referring to the iron sulfate calibration curve (6.4, 3.2, 1.6, 0.8, 0.4 and 0.2 mg/ml) and expressed as the FRAP value (millimoles Fe (II) per gram sample).…”
Section: Methodsmentioning
confidence: 99%
“… 12 Another study found that solid-state fermentation of Aspergillus cristatus could increase the content of protopanaxadiol and protopanaxatriol in Panax notoginseng and exert anti-aging activity. 13 However, Panax notoginseng has various types of active ingredients, and the content of active substances, antioxidant capacity and safety of Panax notoginseng fermented by Saccharomyces cerevisiae have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…(3) The process yields higher-quality and more active fermentation products [ 13 ]. (4) Microbial fermentation enhances Chinese herbal medicine, promoting water and energy conservation while reducing waste [ 14 ]. Microbial fermentation has therefore emerged as a sustainable, energy-efficient, and effective technique.…”
Section: Introductionmentioning
confidence: 99%